Best interests and the sanctity of life after W v M. Issue 9 (21st November 2012) - Mullock, Alexandra
Abstract : The case of W v M and Others, in which the court rejected an application to withdraw artificial nutrition and hydration from a woman in a minimally conscious state, raises a number of profoundly important medico-legal issues. This article questions whether the requirement to respect the autonomy of incompetent patients, under the Mental Capacity Act 2005, is being unjustifiably disregarded in order to prioritise the sanctity of life. When patients have made informal statements of wishes and views, which clearly—if not precisely—apply to their present situation, judges should not feel free to usurp such expressions of autonomy unless there are compelling reasons for so doing.